Anatomical and functional outcomes of surgery of rhegmatogenous retinal detachment - Sharma, H; Joshi, SN; Shrestha, JK (Nepalese Journal of Ophthalmology, 2010)
Introduction: Rhegmatogenous retinal detachment (RRD) is a potentially blinding condition. Objective: To evaluate the anatomical and functional outcome of surgery of RRD. Materials and methods: A prospective study of interventional case series was designed including 50 consecutive patients with RRD in a tertiary level eye center in Kathmandu. The patients underwent scleral buckling (SB) or pars plana vitrectomy (PPV) according to the proliferative vitreo-retinopathy (PVR) changes. All the patients had at least 3 months of follow-up. The anatomical and physiological outcome measures were primary retinal reattachment and improvement in visual acuity respectively. The surgery was considered successful when there was attachment of retina after the first surgery. Results: The mean age of these patients at the time of presentation was 46.24 ± 19.82 years. Of 50, sixty-six percent of the patients underwent SB and 34 % underwent PPV. Primary surgical success rate was 88 %. While comparing the initial best corrected visual acuity (BCVA) with the final, 72% had an improvement, 12 % unchanged and 16 % had a deteriorated visual acuity. Conclusion: The visual acuity improves and the anatomical success rate is high in the majority of the patients after surgery for rhegmatogenous retinal detachment. Keywords: rhegmatogenous retinal detachment; scleral buckling; pars plana vitrectomy; anatomical outcome; physiological outcome DOI: 10.3126/nepjoph.v2i2.3720 Nep J Oph 2010;2(2) 132-137